PEMUNGUTAN PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) KABUPATEN KARAWANG - R. Bagus Irawan; Novi Dianah (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2018)
The regulation of the arising of tax payable in the area of ​​income tax and BPHTB in the transfer of land and building rights determines state tax revenue. This research is a normative juridical study because this research focuses on comprehensive, systematic and accurate library research integrated with normative research using field data and related regulations. The results of this study confirm that the authority and efforts to resolve the Karawang District Bapenda in tax collection in the field of land and building acquisition fees (BPHTB) are carried out based on Karawang District Regulation No. 4 of 2011 concerning the Fees for Obtaining Land and Building Rights and its procedures are regulated in Karawang Regent Regulations. Although obstacles will always occur in every implementation of government. The cost of acquiring land and building rights (BPHTB) in its implementation is simple, easy because it does not use a tax assessment letter. Taxpayers directly pay the amount of tax owed without notification from the KPPBB.